Evaluation of lens distortion errors using an underwater camera system for video-based motion analysis - Poliner, J.; Fletcher, L.; Klute, G. K. (1993)
When reviewing these results, several points should be noted. First, this study utilized a two-dimensional analysis algorithm. A limitation of the study was that exactly four calibration points were required to define the scaling from screen coordinates to actual coordinates. The use of more than four points would likely result in less variability. Second, all coordinates and calculated errors were normalized to dimensions of the image. Although there were many possibilities for the choice of dimension (e.g., horizontal, vertical or diagonal image size; maximum horizontal, vertical, or diagonal coordinate; average of horizontal and vertical image size or maximum coordinate; etc.), the dimensions used to normalize were assumed to best represent the image size.